Colorectal cancer: Insufficient screening and advanced-stage diagnosis. A retrospective analysis at a public, tertiary-level hospital in Santa Fe (2020-2024) (SigMe, 2025)
Colorectal cancer, the third most common cancer worldwide and the second cause of death in Argentina, has an alarming mortality rate and insufficient screening coverage. This study aims to analyze patients diagnosed with colorectal cancer at a public tertiary-level hospital in Santa Fe between 2020 and 2024, comparing the prevalence between those diagnosed by screening methods and diagnosis based on symptoms. A retrospective analysis of medical records was performed, evaluating variables such as age, family history, risk factors, and adherence to screening. The results showed that 79% of patients did not undergo screening prior to diagnosis, so the disease was diagnosed at an advanced stage with symptoms such as abdominal pain and bleeding. These findings underscore the need for improving screening programs, and for raising awareness for early detection, particularly in the population with family history or modifiable risk factors.
Keywords: Colorectal cáncer; Screening; Signs and symptoms; Chronic disease; Colonoscopy; Occult blood in fecal matter